XEN Gel Stent in Pediatric Glaucoma. Issue 4 (April 2020) - Smith, Oluwatosin U.; Grover, Davinder S.; Emanuel, Mathew E.; Godfrey, David G.; Fellman, Ronald L.
Abstract : Purpose: To report a series of 3 eyes of 3 children with congenital glaucoma receiving the XEN gel stent implant. Patients and Methods: An interventional case series is reported. Results: Three eyes underwent implantation of the gel stent. In 2 cases, the gel implant procedure was performed after failed trabeculotomy, while in the third eye, primary gel stent implantation was performed. One eye received 2 implants. Three procedures were performed via an ab interno approach while the fourth was performed ab externo . No device-related complications were observed. In all 3 eyes, intraocular pressure was controlled without the use of topical medications through 6 to 24 months of follow-up. Conclusions: The gel stent implant can be safely used in children with congenital glaucoma and effectively lowers intraocular pressure in these eyes. This procedure is a viable follow-up to, or replacement for, traditional angle surgery in eyes with congenital glaucoma.